Bone microstructure of mice after prolonged taurine treatment - Martiniakova, M; Sarocka, A; Babosova, R; Galbavy, D; Kapusta, E; Goc, Z; Formicki, G; Omelka, R (Physiological research, 2019)
Taurine, a sulphur - containing amino acid, has been termed a functional nutrient. Its synthetic form is a common ingredient in supplements and energy drinks. There is no information concerning taurine impact on bone microstructure after prolonged supplemental use. Also, differences in bone parameters of mice following taurine exposure are unknown. In this study, a detailed microstructure of compact and trabecular bone tissues of mice subchronically exposed to taurine was determined. Animals (n=12) were segregated into three groups: E1 group - mice received 20 mg/kg b.w. of taurine per day during 8 weeks; E2 group - mice were fed by taurine at a dose of 40 mg/kg b.w. for 8 weeks and a control (C) group. Decreased density of secondary osteons, increased sizes of primary osteon's vascular canals (P<0.05) were observed in taurine - treated animals. Cortical bone thickness, trabecular thickness were decreased (P<0.05) in E1 group, and relative volume of trabecular bone was lower (P<0.05) in E2 group as compared to C group. According to our results, prolonged taurine exposure at the doses used in this study can negatively affect both compact and trabecular bone tissues microstructure.
Keywords: kostní denzita; myši; rozvrh dávkování léků; taurin; Drug Administration Schedule; Animals; Femur; Random Allocation; Taurine; Cortical Bone; femur; zvířata; Mice; náhodné rozdělení; Bone Density; kortikální kost